Toward hard yet tough CrAlSiN coatings via compositional grading - Wang, Yu Xi (2013)
A set of CrAlSiN coatings was synthesized in homogenous and graded composition via magnetron sputtering in mixed Ar and N2 ambient. The microstructures are investigated using glancing angle X-ray diffractometry, field emission scanning electron microscopy and transmission electron microscopy. With compositional grading, CrAlSiN coatings exhibit much improved scratch adhesion strength and better crack propagation resistance at a little expense of hardness.